Digital Transformation in the Mining Sector: Exploring Global Technology Trends and Managerial Issues - Lazarenko Yuliia (EDP Sciences, 2021)
Across the industries, management faces increasing pressure to make digital transformation a strategic priority and embrace the opportunities offered by digitalization, and the mining sector is not an exception in this regard. Whereas it is recognized that within the mining industry digitalization will be a driving force that has a great potential to transform the nature of companies and their interaction with stakeholders at every stage of the value chain, there seems to be a lack of an understanding as to what should be investigated from a managerial perspective for the successful undertaking of the digital transformation initiatives. The paper aims to provide a descriptive overview of the global industry trends with regard to digital technologies in the mining sector, as well as develop a conceptual digital transformation framework that is intended to improve business’ digitization processes for the mining companies by identifying the core managerial areas on which attention should be focused in order to ensure effective implementation of the digital transformation strategy. These main action fields, along with optional additional dimensions could be further elaborated depending on the organizational context and industry environment, and should be taken into consideration when planning and organizing activities directed at delivering effective digital transformations.